2018
DOI: 10.2967/jnumed.118.213140
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Based In Vivo PET Imaging Detects Amyloid-β Reduction in Alzheimer Transgenic Mice After BACE-1 Inhibition

Abstract: Visualization of amyloid-β (Aβ) pathology with PET has become an important tool for making a specific clinical diagnosis of Alzheimer disease (AD). However, the available amyloid PET radioligands, such as 11C-Pittsburgh compound B, reflect levels of insoluble Aβ plaques but do not capture soluble and protofibrillar Aβ forms. Furthermore, the plaque load appears to be fairly static during clinical stages of AD and may not be affected by Aβ-reducing treatments. The aim of the present study was to investigate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…The highest retention was observed in areas of abundant Aβ deposition, especially cortex, hippocampus, and thalamus, and also to some extent in the cerebellum, where pathology starts to emerge at this age. 23,30 This pattern resembles what we have previously reported for brain penetrating Aβ antibodies 30 and represents successful transcytosis of [ 125 I]Bapi-TXB2 across the BBB of brain capillaries. This was confirmed by nuclear track emulsion autoradiography in combination with immunostaining of Aβ and the vascular marker CD31, demonstrating that [ 125 I] Bapi-TXB2 crossed the BBB to interact with parenchymal Aβ pathology, while [ 125 I]Bapi did not, and that hot spots of Bapi were found around vessels with adjacent Aβ pathology.…”
Section: Discussionsupporting
confidence: 85%
“…The highest retention was observed in areas of abundant Aβ deposition, especially cortex, hippocampus, and thalamus, and also to some extent in the cerebellum, where pathology starts to emerge at this age. 23,30 This pattern resembles what we have previously reported for brain penetrating Aβ antibodies 30 and represents successful transcytosis of [ 125 I]Bapi-TXB2 across the BBB of brain capillaries. This was confirmed by nuclear track emulsion autoradiography in combination with immunostaining of Aβ and the vascular marker CD31, demonstrating that [ 125 I] Bapi-TXB2 crossed the BBB to interact with parenchymal Aβ pathology, while [ 125 I]Bapi did not, and that hot spots of Bapi were found around vessels with adjacent Aβ pathology.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, we found a highly stable background signal in WT mice in treatment and vehicle groups using the amyloid ligand [ 18 F]-florbetaben, which encourages the use of the mouse model in combination with the earlier-validated quantification method 16 . A recent PET study showed the ability to detect non-fibrillar Aβ forms in vivo during treatment of transgenic ArcSwe mice with another BACE1 inhibitor 23 , whereas our PET ligand binds only fibrillary parts of the plaque. Future monitoring regimes could therefore entail dual PET with selective tracers to capture both components of amyloidosis during BACE1 inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, data demonstrate a potential role of BACE1 in vessel-localized Aβ production and vascular Aβ deposition. The BACE1 inhibitor NB-360 attenuates Aβ in preclinical AD models [115,116], and was recently investigated in the APPDutch CAA mouse model [117]. APPDutch mice develop leptomeningeal and cortical CAA composed primarily of Aβ40, without exhibiting parenchymal plaques.…”
Section: Limited Efficacy Of Aβ-targeted Therapeutics On Vascular Amymentioning
confidence: 99%